Perbedaan Pemahaman Konsep Matematika Antara Penggunaan Metode Talking Stick Dan Pair Check Ditinjau Dari Gaya Belajar Siswa - Pradipta Annurwanda; Rizki Nurhana Friantini (Jurnal Edumatic : Jurnal Pendidikan Matematika, 2021)
Abstract— This study aims to determine the differences in understanding the concepts ofmathematics subjects from each learning method, learning style and the interaction of both.This research is a quantitative research with a 3x3 factorial design. The population in thisstudy were all eighth grade students of Maniamas Ngabang Middle School 2019/2020academic year totaling 105 people. Samples were taken by cluster random samplingtechnique with a total sample of 78 people. The instrument used was a test instrument tomeasure understanding of mathematical concepts and questionnaire instruments to measurestudent learning styles. The data analysis technique uses two-way variance (two way ANOVA)with a significant level of 5%. Based on the results of the calculation of the hypothesis testcan be concluded (1) There are differences in understanding the concept of mathematicssubjects between the use of the Talking Stick method, Pair Check and conventional materialrelations and functions, namely (a) Students taught by the Talking Stick and Pair Checkmethod produce understanding mathematical concepts the same is good, (b) Students taughtwith the Talking Stick method are better than students taught with conventional methods and(c) Students taught by the Pair Check method are better than students taught by conventionalmethods. (2) There is no difference in understanding of the concepts of mathematical subjectsbetween students who have visual, auditory and kinesthetic learning styles and (3) There is nointeraction of understanding mathematical concepts between each learning method andlearning style.